THE REVIEW OF THE MONOGRAPH: Nisnevich Yu. “Politics and Corruption: Corruption as a Factor of the Global Political Process”. Moscow: Uright Publishing House, 2017. 240 p - Glebov, V.A.; Amiantova, I.S. (RUDN Journal of Political Science, 2018)
The new book by Yu.A. Nisnevich, PhD in Political Studies, is of both scientific and practical interest to political analysts, politicians, federal and regional government officials, students in higher educational institutions. This book by the full professor of the Department of Political Studies in the National Research University “Higher School of Economics” successfully attempts to instrumentally conceptualize and measure corruption. It analyzes the quality of implementing polyarchic democracy rules today, it offers a comparative analysis of authoritarian-like states. By taking the corruption factor into account, it provides empirical cauterization if democratic states. The author raises topical issues: analysis of corruption as a dominant factor of the world political process. The following issues are of particular interest: analysis of motivation of corruption in the public sphere and measures to counteract this behavior.